Attempting integral:

$$-\int \frac{dx}{\sqrt{x^2-9}}$$

Let $x = 3\ sec\ \theta$ so that under the square root we have:

$$\sqrt{9\ sec^2\ \theta - 9}$$

$$\sqrt{9(sec^2\ \theta - 1)}$$

$$\frac{dx}{d\theta} =3\ sec\ \theta\ tan\ \theta$$

The $1/3$ and the $3$ cancel eachother out outside the integral, so we have:

$$-\int \frac{sec\ \theta\ tan\ \theta\ d\theta}{tan\ \theta}$$

The $tan\ \theta$ terms cancel, so we're left to integrate $sec\ \theta$ which is equal to:

$$- \ln\ (tan\ \theta + \ sec\ \theta) + C$$

Since $tan\ \theta = \sqrt{x^2-9}\ $ since it replaced it in the integral, and $sec\ \theta = \frac{x}{3}$, the answer is:

$$-\ ln\ (\sqrt{x^2-9}\ + \frac{x}{3})+C$$

However, using an online calculator, the answer turned out to be:

$$-\ ln\ (\sqrt{x^2-9}\ + x)+C$$

It seemed to come about due to their substitution of $u = \frac{x}{3}$ we led them to get the standard integral of $sec^{-1}x$, which would imply that

$$\sqrt{\frac{x^2}{9} - 9}$$

becomes $$\sqrt{u^2 - 1}$$

And I just don't see how. Can someone explain why what they did is valid and/or where my mistake was?


Your mistake:

$$\sec\theta=\frac x3$$ yields

$$\cos\theta=\frac 3x,\\\sin\theta=\sqrt{1-\frac9{x^2}},\\\tan\theta=\sqrt{\frac{x^2}9-1}.$$

Not $\sqrt{x^2-9}$.

This said, you can rescale the variable with $x=3t$ to get


You may recognize another familiar integral,

$$\int\frac{dt}{\sqrt{1-t^2}}=-\arccos t+C.$$

What you have here is just the hyperbolic equivalent,

$$\int\frac{dt}{\sqrt{t^2-1}}=\text{arcosh }t+C,$$

which can also be written




If $x=3\sec\theta$

$$\tan^2\theta=\left(\dfrac x3\right)^2-1=\dfrac{x^2-9}9$$




  • $\begingroup$ Oh right, so I forgot that $1/3$ is part of the expression for $tan\ \theta$ here, and that'll cancel out the $1/3$ in both terms in the solution? And the $ln\ 3$ bit wasn't in the solution on the calculator.. odd $\endgroup$ – sangstar Jul 11 '17 at 7:05
  • $\begingroup$ @sangstar, As $$-\ln3+C=C'$$ But don't miss the modulus. $\endgroup$ – lab bhattacharjee Jul 11 '17 at 7:06
  • $\begingroup$ Your answer makes sense and I appreciate the help, however I have two quick questions. a) Modulus because $\tan\ \theta$ must be larger than $\sec\ \theta$ for all $\theta$? b) I find it odd that integrating an indefinite integral spits out the constant $ln\ 3$. In this case, what influence is $ln\ 3$ doing to $C'$ to make it differ from $C$? $\endgroup$ – sangstar Jul 11 '17 at 7:52
  • $\begingroup$ @sangstar, $\tan\theta$ can be $<0$ unlike $$\dfrac{\sqrt{x^2-9}}3$$ right? Difference of constant is constant right? $\endgroup$ – lab bhattacharjee Jul 11 '17 at 8:04
  • $\begingroup$ That's right. And yeah, of course, I've just never had a constant come out from a definite integration before I don't think. $\endgroup$ – sangstar Jul 11 '17 at 8:06

$$\int\frac{dx}{\sqrt {x^2-9}}$$

By substitution

$$x=3\sec\theta $$

$$dx=3\sec\theta \tan \theta d\theta$$

$$\int \frac{3\sec\theta \tan \theta d\theta}{\sqrt{9\sec^2\theta-9}} $$

$$\int \frac{3\sec\theta \tan \theta d\theta}{3\tan\theta} $$

$$\int \sec\theta d\theta $$

$$ ln|\sec\theta+\tan\theta|$$

$$ ln| \frac{1+\sin \theta}{cos \theta}|$$

$$ \cos \theta=\frac{3}{x}$$

Recall that $\sin \theta= \sqrt{1-\cos^2\theta}$


$$ ln|x+\sqrt{x^2-9}|-ln3$$


$$I = -\int \frac{1}{\sqrt{x^2-9}}\,dx$$ $\sqrt{bx^2 - a} \implies x = \sqrt{\frac{a}{b}}\sec \alpha$ $$x = 3\sec\alpha \implies \frac{dx}{d\alpha}=3\sec\alpha\tan\alpha$$

$$ -\int \frac{1}{\sqrt{\left(3\sec \alpha \right)^2-9}}3\sec\alpha\tan\alpha\,\,d\alpha$$ $$ -\int \frac{\sec\alpha \tan\alpha}{\sqrt{\sec^2\alpha-1}}\,d\alpha$$ $\sec^2\alpha = 1 + \tan^2\alpha$ $$ -\int \frac{\sec\alpha \tan\alpha}{\sqrt{\tan^2\alpha}}\,d\alpha = -\int \frac{\sec\alpha \tan\alpha}{\tan\alpha}\,d\alpha = -\int\sec\alpha\,d\alpha$$ $$-\int\sec\alpha\,d\alpha = -\ln(\tan\alpha + \sec\alpha) +C$$ $$\alpha = arcsec\left( \frac{1}{3}x\right)$$ $$-\ln\left(\tan\left( arcsec\left( \frac{1}{3}x\right)\right)+ \sec\left( arcsec\left( \frac{1}{3}x\right)\right)\right) +C$$

$$-\ln\left(\sqrt{\frac{1}{9}x^2 -1} + \frac{1}{3}x\right)+C$$

$$-\ln\left(\frac{1}{3} \left(\sqrt{x^2 - 9} + x\right)\right)+C$$

$$-\ln\left(\sqrt{x^2 - 9} + x\right) - \ln(3)+C$$

$$I = -\ln\left(\sqrt{x^2 - 9} + x\right) +C$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.